2018
DOI: 10.1007/978-3-319-99731-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Fano Resonances in Flat Band Networks

Abstract: Linear wave equations on Hamiltonian lattices with translational invariance are characterized by an eigenvalue band structure in reciprocal space. Flat band lattices have at least one of the bands completely dispersionless. Such bands are coined flat bands. Flat bands occur in fine-tuned networks, and can be protected by (e.g. chiral) symmetries. Recently a number of such systems were realized in structured optical systems, exciton-polariton condensates, and ultracold atomic gases. Flat band networks support c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The details of the impact of the DC field direction, and the extension to dimension d = 3 are still waiting to be explored. Perturbed compact localized states from a flat band act as Fano scatterers for dispersive waves and can be useful for spectroscopy [178].…”
Section: Discussionmentioning
confidence: 99%
“…The details of the impact of the DC field direction, and the extension to dimension d = 3 are still waiting to be explored. Perturbed compact localized states from a flat band act as Fano scatterers for dispersive waves and can be useful for spectroscopy [178].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of different types of perturbations have been studied in several examples of flat band networks [9,10], as well as the effects of disorder and nonlinearity and interaction between them [11]. Further studies focused on non-Hermitian flat band networks [12], topological flat Wannier-Stark bands [13], Bloch oscillations [14], Fano resonances [15], fractional charge transport [16] and the existence of nontrivial superfluid weights [17]. Chiral flat band networks revealed that CLS and their macroscopic degeneracy can be protected under any perturbation which does not lift the bi-partiteness of the network [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such peaks are the signs of the SLSs induced by the FBs. Note that the SLSs can change into the compact localized states (CLSs) [50,51] by gapping the FBs away from the dispersive energy spectrum [52]. The CLSs are ideal candidates for the transmission of information [53].…”
Section: Slss and Optical Absorption Without External Electric Fieldmentioning
confidence: 99%